2020
DOI: 10.14740/jocmr4261
|View full text |Cite
|
Sign up to set email alerts
|

Serum Irisin Levels and Clinical Implication in Elderly Patients With Type 2 Diabetes Mellitus

Abstract: Background The aim of this study is to evaluate the level and role of serum irisin in elderly patients with type 2 diabetes mellitus (T2DM) using case-control study. Methods A total of 71 patients with T2DM were selected as the case group according to the inclusion criteria and exclusion criteria; and the ratio of 1:1 was calculated according to the inclusion rate of the residents. The cohort established in Guankou Town, Jimei District, Xiamen City, Fujian Province, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
14
0
3
Order By: Relevance
“…Irisin levels can provide new avenues for controlling age-related muscle changes since it's a potential biomarker for muscle dysfunction that could portend the onset of sarcopenia [19]. Irisin levels were studied in elderly patients with diabetes it was lower than the control group of healthy subjects with the same gender characteristics and age with a difference of ± 5 years old [20]. On the other hand, serum adropin concentrations are negatively associated with renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Irisin levels can provide new avenues for controlling age-related muscle changes since it's a potential biomarker for muscle dysfunction that could portend the onset of sarcopenia [19]. Irisin levels were studied in elderly patients with diabetes it was lower than the control group of healthy subjects with the same gender characteristics and age with a difference of ± 5 years old [20]. On the other hand, serum adropin concentrations are negatively associated with renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Irisin, a new adipocytokine, is released, activated, and transported to a variety of tissues and organs to carry out its physiological tasks. It can, for example, improve insulin resistance, boost uncoupling protein‐1 expression, convert white fat into brown fat with catabolic properties, increase energy consumption and glucose utilization, and coordinate the treatment of metabolic illnesses like obesity and type 2 diabetes (Jung et al, 2017 ; Rizk et al, 2016 ; Xuan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A list of the animal and human study papers to note is summarized in Table 1 [16,20,34,37,50,54,70,[134][135][136]138,139,[141][142][143][144][145].…”
Section: Human Studiesmentioning
confidence: 99%
“…María et al proposed that in individuals with obesity, FNDC5 expression in muscle was significantly decreased in association with T2DM, and FNDC5 expression in muscle was significantly associated with FNDC5 and UCP1 expression in visceral adipose tissue [ 133 ]. In most clinical studies, irisin levels of patients with pre-diabetes or T2DM have been reported to be lower than the controls [ 134 , 138 , 139 ]. The factor that is responsible for the low secretion of irisin in T2DM has not yet been identified, although some studies have suggested that chronic hyperglycemia and hyperlipidemia are possible causes [ 37 , 70 ].…”
Section: Effects Of Irisin On Muscle Glucose Homeostasismentioning
confidence: 99%